Juridical Review of the Role of Notaries in the Implementation of Anti Money Laundering Programs - Muhammad Yusli Juliansyah; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The Notary profession is always guided by the prevailing laws and regulations including Law Number 30 of 2004 as amended by Law Number 2 of 2014 concerning Notary Positions. This study aims to illustrate the role of Notaries in the implementation of anti-money laundering programs as stipulated in Government Regulation Number 43 of 2015 concerning Reporting Parties in the Prevention and Delivery of Anti-Money Laundering Crimes submitted to the Center for Financial Transaction Reporting and Analysis (PPATK). Based on this description, this study uses the Normative Juridical research method